2018
DOI: 10.1155/2018/7965071
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin: A New Regulator of Female Reproductive System

Abstract: Adiponectin is the hormone that belongs to the group of adipokines, chemical agents mainly derived from the white adipose tissue. The hormone plays pleiotropic roles in the organism, but the most important function of adiponectin is the control of energy metabolism. The presence of adiponectin and its receptors in the structures responsible for the regulation of female reproductive functions, such as hypothalamic-pituitary-gonadal (HPG) axis, indicates that adiponectin may be involved in the female fertility r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0
5

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 104 publications
3
27
0
5
Order By: Relevance
“…Thus, high levels of leptin promote onset of puberty in girls via secretion of kisspeptin, and estrogen stimulates leptin secretion additionally. Moreover, adiponectin can affect the HPG axis due to the expression of adiponectin receptors in the hypothalamus, pituitary gland, and gonads . In detail, adiponectin is a regulator of puberty onset as it inhibits the secretion of kisspeptin and GnRH in the hypothalamus and the release of GH and LH in the pituitary gland, and thereby inhibiting the onset of puberty (Figure ) .…”
Section: The Onset Of Puberty In Girlsmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, high levels of leptin promote onset of puberty in girls via secretion of kisspeptin, and estrogen stimulates leptin secretion additionally. Moreover, adiponectin can affect the HPG axis due to the expression of adiponectin receptors in the hypothalamus, pituitary gland, and gonads . In detail, adiponectin is a regulator of puberty onset as it inhibits the secretion of kisspeptin and GnRH in the hypothalamus and the release of GH and LH in the pituitary gland, and thereby inhibiting the onset of puberty (Figure ) .…”
Section: The Onset Of Puberty In Girlsmentioning
confidence: 99%
“…Moreover, adiponectin can affect the HPG axis due to the expression of adiponectin receptors in the hypothalamus, pituitary gland, and gonads . In detail, adiponectin is a regulator of puberty onset as it inhibits the secretion of kisspeptin and GnRH in the hypothalamus and the release of GH and LH in the pituitary gland, and thereby inhibiting the onset of puberty (Figure ) . Individuals with obesity often have low levels of adiponectin .…”
Section: The Onset Of Puberty In Girlsmentioning
confidence: 99%
See 2 more Smart Citations
“…Pieces of evidence also indicated the role of adiponectin in the regulation of reproduction. Studies have also demonstrated that adiponectin plays a role in the regulation of reproduction at both central and peripheral level (Dobrzyn et al, ). At the central level, adiponectin receptors AdipoR1 and AdipoR2 are expressed in hypothalamus and pituitary in human (Kubota et al, ; Rodriguez‐Pacheco et al, ).…”
Section: Introductionmentioning
confidence: 99%